Marketing Strategy of Kedai Karya Online Shop to Increase Sales - Khusnul Yakin; Ike Ratnasari (Journal of Economics, Business, and Government Challenges, 2018)
This research aims to determine the marketing stategy of Kedai Karya Online Shop in increaseasing sales and and to know the factors that influence the fluctuation of sales turnover in Kedai Karya Online Shop. Informants of this research is the owner of Kedai Karya Online Shop. Sources of data collected from interviews, documentation, and observation. Data analysis techniques using interactive analysis techniques include data reduction, data presentation, and conclusions. The results show that Kedai Karya Online Shop use e-marketing strategy that is product strategy, price, communication, and distribution. Factors that influence an increase in sales turnover are seasonal factors, innovation factors, and use of paid advertising. Then the factors that affect the decline in sales turnover is the lack of promotion.